(untitled) (Physical Education, Health and Social Sciences, 2026)
Background: The rapid proliferation of financial technology (FinTech) platforms has fundamentally transformed debt financing landscapes across emerging economies. In Pakistan, where sports communities remain financially underserved, athletes increasingly encounter novel digital lending instruments with limited financial literacy to navigate associated risks. This cross-sectional study examines the role of FinTech adoption in shaping debt financing decisions among professional and semi-professional athletes in Pakistan, with a specific focus on financial awareness and risk perception. Methods: A structured questionnaire was administered to 312 athletes drawn from cricket, hockey, football, kabaddi, and squash communities across Lahore, Karachi, Islamabad, and Peshawar. The instrument measured FinTech awareness, digital lending utilization, financial risk perception, and debt financing behavior. Descriptive statistics, Pearson correlation analysis, and multiple linear regression were employed for data analysis using SPSS v.26. Results: Findings reveal that 68.3% of respondents had utilized at least one FinTech platform for borrowing purposes, yet only 29.5% demonstrated adequate comprehension of associated interest rate structures and repayment obligations. FinTech awareness (β = 0.412, p < 0.001) and risk perception (β = −0.287, p < 0.01) were significant predictors of debt financing decisions. Athletes in individual sports exhibited higher FinTech utilization but lower financial risk awareness compared to team sport athletes. Education level and income stability emerged as significant moderating variables. Conclusions: The study underscores a critical financial literacy gap within Pakistani sports communities despite growing FinTech adoption. Policy recommendations include embedding financial education modules in national sports federations’ athlete development programs, creating sport-specific digital financial literacy campaigns, and regulating predatory digital lending targeting athletes. This research contributes to the nascent literature on FinTech adoption in non-traditional financial contexts within South Asian emerging markets.